2014
DOI: 10.1515/zkri-2014-1732
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal paracrystals

Abstract: Spatially interacting Gaussian random variables arranged on a hexagonal lattice are used to construct examples of hexagonal paracrystals. As for previously described paracrystals on a square lattice the distributions may be specified by a variance, 2 , L σ defining the magnitude of the displacement away from the underlying perfect lattice together with parameters defining transverse and longitudinal correlations (ρ T and ρ L ) between neighbouring displacements. A strong longitudinal correlation indicates a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Alternatively, the diffuse hexagons could arise from disorder within the unit cell of isolated, individual nanosheets. Welberry demonstrated that deviations within the lattice vector direction within a plane of atoms can lead to these diffuse hexagons . Given the sharp (110) diffraction planes in the AI-spXRD, we conclude that the diffuse hexagons observed in Figure c,d arise from variations of the unit cell lattice vector direction within an isolated nanosheet.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Alternatively, the diffuse hexagons could arise from disorder within the unit cell of isolated, individual nanosheets. Welberry demonstrated that deviations within the lattice vector direction within a plane of atoms can lead to these diffuse hexagons . Given the sharp (110) diffraction planes in the AI-spXRD, we conclude that the diffuse hexagons observed in Figure c,d arise from variations of the unit cell lattice vector direction within an isolated nanosheet.…”
Section: Resultsmentioning
confidence: 66%
“…Welberry demonstrated that deviations within the lattice vector direction within a plane of atoms can lead to these diffuse hexagons. 64 Given the sharp (110) diffraction planes in the AI-spXRD, we conclude that the diffuse hexagons observed in Figure 5c,d arise from variations of the unit cell lattice vector direction within an isolated nanosheet. Moreover, we find that both EM-and HS-SiNSs are very sensitive to the beam, with the ED patterns transforming into diffuse rings over the course of a few seconds (Figure S7).…”
Section: ■ Results and Discussionmentioning
confidence: 67%